Investigation of in-vivo inhibition of β-lactamase by β-lactamase inhibitor protein - Akkaya, Ayşe Ezgi. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2010., 2010)
β-lactam antibiotics, which target transpeptidase enzymes that synthesize the bacterial cell wall, are the most widely utilized antimicrobial agents. However owing to the widespread usage, bacteria acquire resistance to these antibiotics. Bacteria produce β-lactamase enzymes to hydrolyze the amide bond of the β-lactam ring and as a result β-lactam antibiotics lose their effectiveness. Thus, the use of β-lactamase inhibitors is an important strategy to activate the therapeutic value of β-lactam antibiotics. In this context, design of β-lactamase inhibitors, which restore the antibiotic activity of β-lactam drugs against resistant pathogens, is an intense area of research. Streptomyces clavuligerus produces a protein inhibitor of β-lactamase called the β-lactamase inhibitor protein (BLIP) composed of 165 amino acids. Recent studies show that BLIP has inhibitory properties against class A β-lactamases such as R-TEM-1. Peptides derived from BLIP also have inhibitory properties. In this work, experimental studies were carried out to investigate in-vivo β-lactamase inhibition by BLIP. For this purpose, BLIP was cloned into expression vector pET-26b(+) and expressed as a periplasmic protein in Escherichia coli BL21(DE3) cells for binding and inhibition studies. In order to investigate in-vivo β-lactamase inhibition in the periplasm, pUC18 plasmid, carrying the gene for R-TEM-1 β-lactamase was transformed into the E. coli cells harboring recombinant pET-26b(+) vector and both BLIP and β-lactamase were expressed. β-lactamase expression was constitutive but BLIP was expressed under the control of the promoter inducible by IPTG. Inhibiton was examined by studying the growth of the recombinant cells, colony forming units, protein analysis and in-vitro β-lactamase activity. The presence of BLIP in the periplasmic fraction was verified by SDS-PAGE analysis. The result of β-lactamase activity measurement can be stated as the inhibition of β-lactamase by BLIP under in-vivo conditions since the activities of the control groups that do not have BLIP (1187.5 U/L) was approximately twice of the periplasmic extracts that have BLIP (571.88 U/L).
Keywords: Beta lactamases.; Beta lactam antibiotics.